R E V I E W : Species diversity of indigenous fruits in Indonesia and its potential - TAHAN UJI (Biodiversitas Journal of Biological Diversity, 2007)
Indonesia is rich of species diversity of indigenous fruits. The results of study reported that there are 266 species of indigenous fruits encountered in Indonesia and 62 species of them are cultivated. Four genera of indigenous fruits are recommended to developed in Indonesia, i.e. Durio, Mangifera, Garcinia and Nephelium. This study also reported that duku (Lansium domesticum), salak (Salacca zalacca), buah merah (Pandanus conoideus), and matoa (Pometia pinnata) have a good prospect also to be developed in Indonesia.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Species diversity, indigenous fruits, potential, conservation, Indonesia